2016
DOI: 10.2196/publichealth.4742
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup Stigma Among Men Who Have Sex with Men: Data Extraction from Craigslist Ads in 11 Cities in the United States

Abstract: BackgroundGay, bisexual, and other men who have sex with men (MSM) regularly experience homophobic discrimination and stigma. While previous research has examined homophobic and HIV-related intergroup stigma originating from non-MSM directed at MSM, less is known about intragroup stigma originating from within MSM communities. While some research has examined intragroup stigma, this research has focused mostly on HIV-related stigma. Intragroup stigma may have a unique influence on sexual risk-taking behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Consequently, intragroup stigma is most commonly applied to people in a group that exhibit the most extreme version of the negative characteristic being stigmatized. Intragroup stigma may be more likely to appear when stigmatized groups are highly heterogeneous or easily stratified (Goldenberg, Vansia, & Stephenson, 2016).…”
Section: Intragroup Stigmamentioning
confidence: 99%
“…Consequently, intragroup stigma is most commonly applied to people in a group that exhibit the most extreme version of the negative characteristic being stigmatized. Intragroup stigma may be more likely to appear when stigmatized groups are highly heterogeneous or easily stratified (Goldenberg, Vansia, & Stephenson, 2016).…”
Section: Intragroup Stigmamentioning
confidence: 99%
“…The advent of HIV testing in the mid-1980s further divided the gay community into two groups, that is, people living with HIV and HIV-unknown (Sheon & Crosby, 2004). After three decades, stigmatizing attitudes toward PLHIV are still highly prevalent in the gay community (Goldenberg, Vansia, & Stephenson, 2016). MSM living with HIV encountered experiences of prejudice, avoidance, and discrimination from members of the gay community (Courtenay–Quirk et al, 2006).…”
Section: Hiv Stigma Within the Gay Communitymentioning
confidence: 99%
“…Twenty-nine percent of surveyed HCF staff in Ghana indicated that if they had a choice, they would prefer not to provide services to MSM [ 15 ]. At the interpersonal level (i.e., MSM peer groups) men may experience, perceive or anticipate HIV, same-sex, and gender non-conforming stigma from their peers [ 16 , 17 ]. These intersecting stigmas manifest through attitudes, gossip, verbal abuse and social isolation of peers who they associate with HIV (regardless of serostatus) and who express their gender identities in ways that do not conform to perceived cultural norms of masculinity (i.e., gender non-conforming) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%